KESALAHAN REPRESENTASI SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA MATERI PERBANDINGAN - Claudya Zahrani Susilo; Susiswo Susiswo; Swasono Rahardjo (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
This study is a qualitative descriptive study that describes the misrepresentation of junior high school students in solving mathematical problems. The research subjects were grade VII students representing high, medium, and low levels of mathematical ability. The results showed that the errors made by students in solving mathematical problems were: (1) high-ability students at the stage of understanding the problem made a verbal representation error, the stage of planning a solution, the stage of carrying out the completion, and the stage of checking the results of making a symbol representation error; (2) moderately capable students at the stage of understanding the problem of making verbal representations and symbol representations, the stage of planning a settlement, the stage of carrying out the settlement, and the stage of checking the results of making symbol representation errors, (3) students with low mathematical abilities at the stage of understanding the problem, the stage of planning a solution , the stage of carrying out the completion, and the stage of checking the results of making symbol representation errors.